2016
DOI: 10.1186/s13075-016-1065-3
|View full text |Cite
|
Sign up to set email alerts
|

The type I interferon signature in leukocyte subsets from peripheral blood of patients with early arthritis: a major contribution by granulocytes

Abstract: BackgroundThe type I interferon (IFN) signature in rheumatoid arthritis (RA) has shown clinical relevance in relation to disease onset and therapeutic response. Identification of the cell type(s) contributing to this IFN signature could provide insight into the signature’s functional consequences. The aim of this study was to investigate the contribution of peripheral leukocyte subsets to the IFN signature in early arthritis.MethodsBlood was collected from 26 patients with early arthritis and lysed directly or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
(20 reference statements)
2
21
1
Order By: Relevance
“…Dysregulation of type-I INFs are often observed in autoimmunity and chronic inflammatory diseases [34][35][36][37]. In a study of at-risk individual for RA, IFN signalling genes were indicative of progression to the inflammatory stage [38][39][40]; however, IFN signatures were no longer reported predictive later in the disease course [35,41,42]. As supported by our data, this suggests that IFN signalling is associated with early pathogenesis, independently of whether this can be exploited clinically later in the disease.…”
Section: Discussionsupporting
confidence: 70%
“…Dysregulation of type-I INFs are often observed in autoimmunity and chronic inflammatory diseases [34][35][36][37]. In a study of at-risk individual for RA, IFN signalling genes were indicative of progression to the inflammatory stage [38][39][40]; however, IFN signatures were no longer reported predictive later in the disease course [35,41,42]. As supported by our data, this suggests that IFN signalling is associated with early pathogenesis, independently of whether this can be exploited clinically later in the disease.…”
Section: Discussionsupporting
confidence: 70%
“…It has been shown that SSZ reduces the levels of RA-related cytokines, such as interleukin-1β and tumor necrosis factor-α [16], suggesting that SSZ might function through overall suppression of inflammatory cytokines, including type I IFNs. Furthermore, it was demonstrated that SSZ is able to accelerate apoptosis of neutrophils [17], which we have recently shown to be major inducers of the type I IFN response in RA [18]. Consequently, suppression of the type I IFN response by SSZ might be mediated via an increase in neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…It is now clear that the developing immune response is influenced by genetic and epigenetic factors [ 41 ]. IFNAR1, IL-21R and IL-23 loci have been reported to play a key role in the pathogenesis of RA [ 83 85 ] and Th17 cells are implicated in pathogenesis especially in the pre-RA phase [ 68 , 72 , 73 ]. Whether the CCS differences we observed represent changes impacting the pre-RA phase or are acquired during the early phase of RA is at present unclear.…”
Section: Discussionmentioning
confidence: 99%